The Wild Things in Japanese: Markedness, Rhythm and Cultural Acceptance - Cheetham, Dominic (Meta, 2011)
The written text of picturebooks is often deceptively simple. However, as Riita Oittinen (2003) shows in her analysis of Swedish, German and Finnish translations of Maurice Sendak’s Where the Wild Things Are (1963), picturebook text can be more complex, or more carefully written than it at first appears. Oittinen examines sentence length and punctuation in relation to rhythm for reading aloud. This study follows and extends her analysis for the Japanese translation. The Japanese translation is dramatically different from the original text – much more so than the translations studied by Oittinen. The conclusion highlights that the Japanese translation is nonetheless a very popular and long selling text within its target culture.